2015
DOI: 10.1016/j.fuel.2015.04.036
|View full text |Cite
|
Sign up to set email alerts
|

Influence of char composition and inorganics on catalytic activity of char from biomass gasification

Abstract: This research investigates the catalytic properties of char which was recovered directly from a biomass gasifier. Poplar wood was gasified in steam and CO 2 environments in a fluidized bed reactor at temperatures ranging from 550 to 920°C. Char was composed of 85% carbon with concentrations of N, H, and S between 0.3% and 3%, depending on gasification conditions. The inorganics (Ca, K, Na, P, Si, Mg) were quantified, revealing that Ca was present in the highest concentration (0.5-1%), followed by K, ranging fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
84
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(88 citation statements)
references
References 35 publications
4
84
0
Order By: Relevance
“…As shown in Table 11, the cations in the biomass reside in biochar after the biochar production processes [145,146]. When biochar is applied to soil, the basic cations contained The CEC of the soil increases with increasing charge density in soil (per unit surface area) and with increasing soil surface area that can adsorb cations [147].…”
Section: Soil Amendmentmentioning
confidence: 99%
“…As shown in Table 11, the cations in the biomass reside in biochar after the biochar production processes [145,146]. When biochar is applied to soil, the basic cations contained The CEC of the soil increases with increasing charge density in soil (per unit surface area) and with increasing soil surface area that can adsorb cations [147].…”
Section: Soil Amendmentmentioning
confidence: 99%
“…The main difference between the FTIR spectra profiles was that sample FC-450 had a slightly higher ACH 2 peak at $2931 cm À1 and a lower SiAOASi peak at 1110 & 798 cm À1 . The FTIR profiles confirmed the presence of oxygen functional groups on the surface, and showed that there were aluminosilicate on the char surface, which was the chief constituents in molecular sieve [13].…”
Section: Function Groups On the Surfacementioning
confidence: 74%
“…It has been reported that oxygen functional groups can play a role in catalytic activity of carbon materials [13]. Therefore functional groups on the char surface were studied.…”
Section: Function Groups On the Surfacementioning
confidence: 99%
See 2 more Smart Citations